The purpose driven church: growth without compromising your message & mission - Warren, Rick (Zondervan Publ. House, 1995)
Jede Gemeinde wird von etwas angetrieben. Traditionen, Programme, Persönlichkeiten, Ereignisse, Suchende und sogar Gebäude können die treibende Kraft einer Gemeinde sein. Rick Warren ist jedoch der Überzeugung, dass eine Gemeinde sich nur dann gesund entwickeln kann, wenn sie vom Auftrag Gottes getrieben wird. Nur dann wird sie zu einer Gemeinde, die: wärmer wird durch Gemeinschaft, tief gehender wird durch Jüngerschaft, stärker wird durch Anbetung, weiter wird durch Dienen und größer wird durch Evangelisation. - The thesis of The Purpose Driven Church is that when churches think first about their health, growth is sure to follow. "If your church is healthy," writes Rick Warren, "growth will occur naturally. Healthy, consistent growth is the result of balancing the five biblical purposes of the church." These five purposes are to "Love the Lord with all your heart," "Love your neighbor as yourself," "Go and make disciples," "[Baptize] them," and "[Teach] them to obey." And those purposes can only be accomplished, argues Warren, when church leaders stop thinking about church-building programs and shift their focus to a "people-building process" involving fellowship, discipleship, worship, and evangelism. Warren, the founder of the fastest-growing Baptist church in American history, has taught seminars to thousands of pastors from all over the world, many of whom have successfully implemented his techniques. In order for a church to be healthy, it must be built around the five purposes give to the church by Jesus. Learn the secret behind the fastest growing Baptist church in America and discover how to make your church warmer through fellowship, deeper through discipleship, stronger through worship, broader through ministry, and larger through evangelism.